The Significance of Uniform for Members of the Women’s Fellowship in the Reformed Church in Zambia - Blok-Sijtsma, Marike (Studies in world christianity, 2026)
A church uniform is a distinctive characteristic of members of ecclesiastical women’s organisations in Southern Africa. This article explores the significance of this uniform for members of the women’s fellowship in the Reformed Church in Zambia. It argues that the uniform is more than just a social identity marker. To the women wearing it, the uniform is also, and perhaps foremost, a religious identity marker: it signifies their commitment to Christianity and pledge to lead a holy life. The women make a lot of sacrifices in terms of time and money to be permitted to wear the uniform; these are, in their view, compensated and rewarded by the esteem and recognition they receive within both the church community and the society at large. Focusing on a women’s fellowship, this study contributes to our knowledge and understanding of a group of women within African Christianity that has been little studied.